(untitled) (Fiep Bulletin - online, 2013)
This project is sized thoughts and theoretical studies of psychologist Jean Piaget, who developed an important work about the thinking and reasoning of children, he divides into four cognitive development stage, which in turn are divided into substages, for such study we will only get to the stages preoperative, operative and postoperative-concrete-formal, since the students to the project which encompasses age is 04 years on.Aiming to develop recreational activities, since the play is very important for children’s development, and it is through play that children learn more about themselves, where they expand their knowledge, talk with adults and children explore objects, learn what the rules are and abide by them, and most importantly socialization group develops, learns that it is essential to integrate all, so people grow without prejudice, and prepared for group work and therefore provide socialization and community integration school.The project includes all manifestations of physical education will be developed with students of the 1st and 2nd cycles of Elementary School with the guidance of a professor of physical education and collaboration in the management, coordination, faculty, staff, and is intended to prepare students for the 3rd and 4 cycles of Basic Education, to develop a role as monitors. Working so social interaction between students and staff.The evaluation will take place continuously in accordance with the participation and involvement of students, individually and in groups, where they will be observed the ability of social interaction and psychomotor development during the year.